The Welfare Effects of Asset Means-Testing Income Support - Felix Wellschmied (Institute for the Study of Labor (IZA), 2015)
This paper quantitatively determines the asset limit in income support programs which minimizes consumption volatility in a lifecycle model with incomplete markets and idiosyncratic earnings risk. An asset limit allows allocating transfers to those households with the highest utility gains from extra consumption. Moreover, it serves as substitute for history and age dependent taxation. However, a low limit provides incentives for high school dropouts to accumulate almost no wealth. Consequently, they miss self-insurance and suffer from high consumption volatility. For an unborn, these effects are optimally traded-off with an asset limit of 145000.
Keywords: D91; I38; J26; 330; means-tested programs; public insurance; incomplete markets